Letter from Georg Bredig to Max Bredig, December 6, 1937 - Bredig, Georg (1937)
Georg Bredig (1868-1944) provides updates to his son, Max Bredig (1902-1977), on immigration paperwork, the shipment of periodicals and other personal to the U.S.A, extended family members, and his health ailments. Georg's tone additionally reveals the increasing difficulties faced by many German Jewish citizens under the Third Reich as the regime escalates antisemitic measures.
Keywords: Third Reich; Antisemitism; Emigration and immigration; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977